Perioperative Management of Craniotomy for Clipping Aneurysm: A Case Report - Taopan, Damatus Try Hartanto; Suarjaya, I Putu Pramana (Fakultas Kedokteran Universitas Pelita Harapan, 2025)
Background: Ruptured cerebral aneurysm is the most common cause of spontaneous subarachnoid hemorrhage (SAH). Anesthesiologists play a critical role in recognizing these complications to ensure thorough pre-anesthetic evaluation and appropriate perioperative management. However, there remains a limited number of case reports detailing the perioperative care of patients undergoing craniotomy for aneurysm clipping. Case Description: We present the case of a 66-year-old woman diagnosed with acute non-communicating hydrocephalus, pan-ventricular intraventricular hemorrhage, and subarachnoid hemorrhage involving the basal cistern, bilateral sylvian fissures, and temporal lobes following ventriculoperitoneal (VP) shunt placement. The hemorrhage was attributed to a ruptured aneurysm. A craniotomy for aneurysm clipping was planned, and the procedure was performed under general anesthesia. Intraoperatively, the patient's hemodynamic parameters were successfully maintained within stable limits. Postoperatively, the patient was closely monitored in the intensive care unit, where no neurological deficits or major complications were observed during the hospital stay. Discussion: This case highlights the complexity of managing patients with aneurysmal subarachnoid hemorrhage, particularly those presenting with multiple complications such as hydrocephalus and intraventricular extension of bleeding. Conclusions: The successful management of this case demonstrates that a well-structured perioperative plan is crucial in the surgical treatment of ruptured aneurysms. Despite the high-risk nature of subarachnoid hemorrhage and its associated complications, favorable outcomes can be achieved with careful preoperative preparation, intraoperative vigilance, and postoperative monitoring. Further case reports and studies are needed to expand the evidence base and refine best practices in the perioperative management of patients undergoing craniotomy for aneurysm clipping.